Chemical bath deposited Nickel oxide thin film as electrode material for pseudocapacitors. Issue 1 (1st October 2022) - Sathyan, T V; Thomas, Nygil; Thomas, Jasmine; Deepa, K.; Remadevi, T L
Abstract : We have synthesized thin films of nickel oxide (NiO) on silver and glass substrates, at very low temperature of 60°C, by chemical bath deposition (CBD) method. The precursor used consists of nickel nitrate and aqueous ammonia. Structural characteristics were studied using x-ray diffraction (XRD) and morphological studies were done using scanning electron microscopy (SEM). Ultraviolet-visible (UV-Vis) spectroscopy was used for optical studies. To investigate electrochemical behaviour of thin film electrode materials, cyclic voltammetry (CV) measurements were conducted. For electrochemical studies the galvanostatic charge/discharge (GCD) tests were also conducted. The formation of face centred cubic NiO structure was confirmed using XRD. The scanning electron microscopy images show uniform distribution of worm-like porous morphology. CV measurements revealed the capacitive behaviour of the films.